KEWENANGAN PENGELOLAAN, PENINGKATAN ANGGARAN DAN PERLUASAN STRUKTUR ORGANISASI PENDIDIKAN MADRASAH - Nurudin Nurudin (Badan Litbang dan Diklat Kementerian Agama RI, 2015)
AbstractThis paper examines various perspectives on the management of madrasah education that include:Firstly, what is the government’s perspective on the management option of madrasah, is it the government’s authority (the Ministry of Religion) or madrasah management option is the authority of local government? Second, Why does the financing of madrasah require increasing portion of the budget that is equivalent to ordinary schools? Third, why do we need improvement and expansion of authority for the managerial organizational structure in the Ministry of religion from the level of directorate to be directorate general level ?. The results of the study are first, the managerial authority of madrasah in the perspective of public administration shows that the management of madrasah is the domain of the government and has been delegated by the government to the Ministry of Religion. Second, the budget implementation for madrasah has not met twenty percent of the State Budget (APBN) as well as from the Regional Budget (APBD) as mandated by the constitution. This non-proportional budgeting has impacted the implementation of madrasah to be non-optimal. Third, the management organization of madrasah education in the Ministry of Religion is not optimal in serving the organization of madrasah. Increased authority and expansion of madrasah education management organization structure is an urgent need in order to balance the scope of development and organizational capacity.AbstrakTulisan ini mengkaji berbagai perspektif tentang pengelolaan pendidikan madrasah meliputi: Pertama Bagaimana perspektif administrasi pemerintahan terhadap pilihan pengelolaan madrasah sebagai kewenangan pemerintah (Kementerian Agama) ataupun pilihan pengelolaan madrasah sebagai kewenangan pemerintah daerah? Kedua, Mengapa pembiayaan madrasah membutuhkan peningkatan porsi anggaran yang setara dengan sekolah? Ketiga, Mengapa dibutuhkan peningkat an kewenangan dan perluasan struktur organisasi pengelola madrasah di Kementerian agama dari level direktorat menjadi direktorat jenderal?. Hasil kajian adalah, Pertama, Kewenangan pengelolaan pendidikan madrasah dalam perspektif administrasi pemerintahan menunjukkan, bahwa pengelolaan pendidikan madrasah merupakan domain pemerintah dan secara delegatif telah diberikan oleh pemerintah kepada Kementerian Agama. Kedua, Anggaran penyelenggaraan pendidikan madrasah belum memenuhi dua puluh persen dari Anggaran Pendapatan dan Belanja Negara (APBN) serta dari Anggaran Pendapatan dan Belanja Daerah (APBD) sebagaimana dimandatkan konstitusi. Penganggaran yang belum proporsional ini telah berdampak terhadap penyelenggaraan madrasah yang tidak optimal. Ketiga, Organisasi pengelola pendidikan madrasah di lingkungan Kementerian Agama belum optimal dalam melayani penyelenggaraan pendidikan madrasah. Peningkatan wewenang dan perluasan struktur organisasi pengelola pendidikan madrasah merupakan kebutuhan mendesak dalam rangka menyeimbangkan antara ruang lingkup pembinaan dan kapasitas organisasi